High prevalence of ESBL encoding genes in enterobacterales isolated from hospital and environmental wastewater in Pakistan- One Health challenge - Muhammad Usman Qamar; Muhammad Rizwan; Fatima Tuz Zahra; Faiqa Arshad; Asma Ejaz; Aatika; Sana Rehman; Zikria Saleem (Molecular Biology Reports, 2026)

Precise dual-gene knockout of MSTN and SOCS2 via cytidine base editing enhances muscling and growth in goats - Ling Li; Ming-Xing Cao; Muhammad Farhab; Paing Oo Kyaw; Shu-Qi Zhao; Yi Zhao; Feng-Lei Chen; Tariq Sohail; Ejaz Ahmad; Shao-Xian Cao; Yu-Guo Yuan (Functional & Integrative Genomics, 2026)

Exogenous dopamine alleviates chilling injury of sapodilla (Manilkara zapota) fruit by modulating reactive oxygen species and ascorbate-glutathione cycle activities - Sajid Ali; Syed Muhammad Kashan Haider; Safina Naz; Hafiz Umer Javed; Aamir Nawaz; Shaghef Ejaz; Muhammad Shahzad Saleem (Postharvest Biology and Technology, 2026)

Seismic and petrophysical evaluation of the Paleocene Lockhart Formation as a fractured carbonate reservoir in the upper Indus Basin, Pakistan - Muhammad Nauman Ejaz; Hua-Wei Zhou; Zohaib Naseer (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Techno-economic assessment of batch reverse osmosis desalination systems: Rating and design - Qais N. Al-Oweiti; Omar G. Kaoud; M.A.M. Ahmed; Faheem Ejaz; Muhammad H. Elbassoussi; Syed M. Zubair (Desalination, 2026)

Foliar Application of Boric Acid Modulates the Morpho-Physiological Attributes and Health Risk Factors of Turnip (Brassica rapa L.) Under Nickel Accumulation Stress - Fizza Sajid; Tahrim Ramzan; Muhammad Shahbaz; Arslan Haider; Ejaz Ahmad Waraich; Sundas Qadeer (Journal of Soil Science and Plant Nutrition, 2026)

Computational identification of natural phytochemicals as potential inhibitors of UBE2J1 causing ovarian cancer - Zujaja Rehman; Ejaz Rasul; Wisha Asif; Rabail Afzal; Nouman Ali; Nimra Hanif; Muhammad Salik Kamran (In Silico Pharmacology, 2026)

Comparative in vitro pathogenicity of different oil-based formulations of Metarhizium anisopliae against three different aphid species - Ahmad Nawaz; Anam Ejaz; Tariq Mustafa; Usman Naeem; Amna Irshad; Muhammad Dildar Gogi; Muhammad Tayyib; Muhammad Naveed; Amjad Abbas; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2026)

In-situ growth of layer double hydroxides on TFC membranes to improve forward osmosis performance - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Woei Jye Lau (Journal of Environmental Chemical Engineering, 2026)

Correlating the Performance of Forward Osmosis Process to the Characteristics of Inorganic Draw Solutions - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Niaz Muhammad; Mohamed Shaban; Sameerah I. Al-Saeedi; A. M. Elbasiony; Woei Jye Lau (Water, Air, & Soil Pollution, 2026)

Flash flood susceptibility assessment using an integrated geomorphologic framework in data-scarce arid and semi-arid regions - Aftab Ullah; Rashid Farooq; Abdul Razzaq Ghumman; Muhammad Ejaz Tanveer; Muhammad Atiq Ur Rehman Tariq (Modeling Earth Systems and Environment, 2026)
Flash floods are among the most frequent natural hazards, posing serious environmental challenges, particularly in arid and semi-arid regions where steep topography and compact basin morphometry accelerate surface runoff. The ungauged hill torrents of southwestern Punjab, Pakistan, are particularly vulnerable to such events, experiencing recurrent, intense flash floods. This study develops an integrated GIS-based morphometric framework to assess flash flood susceptibility across 13 major hill torrents in DG Khan and Rajanpur, Punjab. Fifteen morphometric parameters were analyzed using three complementary approaches: Hazard Degree (HD), Principal Component Analysis (PCA), and Analytical Hierarchy Process (AHP). The HD method captured the cumulative influence of all parameters. At the same time, PCA reduced redundancy and identified four dominant controlling factors: length of overland flow (Lo), form factor (Ff), circulatory ratio (Rc), and ruggedness number (Rn). The AHP further incorporated expert judgment, identifying drainage density (Dd) and ruggedness number as the most influential parameters, followed by basin relief (Bh) and drainage frequency (Fs). The convergence of results across the three independent methods significantly improves classification reliability compared to single-method analyses. Three hill torrents (Vidore, Mithawan, and Kaha) were consistently classified as highly susceptible, one as moderately susceptible, and four as low susceptibility. Hence, the proposed integrated HD-PCA-AHP model reduces methodological uncertainty and provides a transferable, data-efficient tool for assessing flash flood susceptibility and managing watersheds in data-scarce arid and semi-arid regions.

Efficacy of Vachellia nilotica Extract-coated Urea in Maize: Field Performance and Phytochemical Basis of Urease Inhibition - Rashid Mahmood; Hina Jabeen; Muhammad Ajmal Rana; Faisal Nadeem; Ejaz Ahmed; Muhammad Bilal Chattha (Journal of Soil Science and Plant Nutrition, 2026)

Thiourea Mediated Improvement of Drought Stress in Maize (Zea Mays L.): Unrevealing Morpho-Physiological, Biochemical, and Root Attributes - Arslan Haider; Ejaz Ahmad Waraich; Surriya Bibi; Tahrim Ramzan; Muhammad Ahmad; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

Multi-scale meteorological and hydrological drought severity in a high-altitude Himalayan basin: An intensity–duration–frequency approach using SPI and SSI (1970–2016) - Nuaman Ejaz; Muhammad Rashid; Muhammad Waqar Saleem; Amro Elfeki; Songhao Shang (Journal of Mountain Science, 2026)

Foliar application of silicon alleviates adverse effect of drought stress by improving growth, physiological attributes, and antioxidant defense of camelina (Camelina sativa L.) - Bilal Ahmad Shahzad; Ejaz Ahmad Waraich; Muhammad Saleem; Saddam Hussain; Saifullah (Acta Physiologiae Plantarum, 2026)

Sustainable Laccase Production by Anoxybacteroides rupiense UE27 Using Desmostachya bipinnata Biomass: Optimisation and Application in Textile Effluent Treatment - Haniah Saeed; Bushra Rehman; Uroosa Ejaz; Maria Muhammad Ashraf; Amal Siraj; Areesha Mustafa; Muhammad Sohail (Environmental Microbiology, 2026)
Laccase has been widely reported for the detoxification of industrial effluents, yet large‐scale applications require cost‐effective production. This study utilised an innovative approach by employing biomass from the halophyte Desmostachya bipinnata, which has not been previously reported for microbial enzyme production. A newly discovered bacterial species, Anoxybacteroides rupiense, was used for laccase production. Initially, the factors impacting laccase production by the thermophilic strain of A. rupiense UE27 (Genome Project JBHLFH010000000.1) were screened for their significant effects using the Plackett–Burman design. Consequently, Response Surface methodology was adopted to optimise the significant factors, resulting in a maximum laccase yield of 51.69 U L −1 at pH 6.39 and in presence of 0.59 mM CuSO 4 , representing a 4.29‐fold increase compared to the unoptimised conditions. AFM revealed comminution in the plant biomass and FTIR analysis confirmed laccase‐mediated lignin degradation in D. bipinnata biomass, evidenced by shifts in aromatic CC (1597–1650 cm −1 ), CH methyl (2850–2918 cm −1 ) and phenolic OH (3300–3400 cm −1 ) regions. Moreover, growth of A. rupiense UE27 in the presence of textile effluent resulted in 70.6% decolourisation with the subsequent laccase production. Hence, this study presents a sustainable and innovative approach for developing wild biomass‐based processes for the cost‐effective production of laccase by thermophilic bacteria.

Acacia (Acacia nilotica) seed oil-based nanoemulsion delays softening of mango fruit by modulating oxidative stress and suppressing cell wall degradation - Shaghef Ejaz; Abdul Manan Abbas; Sajid Ali; Muhammad Azam; Mehdi Maqbool; Muhammad Saqib; Muhammad Abid (Journal of Stored Products Research, 2026)

Silver nanoparticles in water disinfection: a comprehensive overview on their mechanisms, benefits, and limitations - Muhammad Shehroz Zafar; Sana Ejaz; Farhan Ahmad; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Faiza Manzoor; Sadia Aziz; Saima Iqbal; Muhammad Adnan Iqbal (Archives of Microbiology, 2026)

Foliar Application of Melatonin and Ascorbic Acid Mitigates Salinity Stress by Improving the Morpho-Physiological, and Antioxidant Defense System in Canola (Brassica Napus L.) - Tahrim Ramzan; Muhammad Shahbaz; Farooq Ahmad; Ejaz Ahmad Waraich (Journal of Soil Science and Plant Nutrition, 2026)

Spinocerebellar Ataxia Type 35 Presenting with Dysphagia in a Patient from Saudi Arabia: A Case Report and Literature Review - Ahmed Attar; Ahmed S. Abduhamid; Mumen H. Halabi; Abdulrahman Bahalaq; Afnan Sibyani; Muhammad Ejaz Ahmed; Yasser Aladdin (The Cerebellum, 2026)

The impact of different air distribution and extraction strategies on the mitigation of airborne infection risk in classroom settings - Muhammad Farhan Ejaz; Simo Kilpeläinen; Panu Mustakallio; Risto Kosonen (Building and Environment, 2026)

Plant-mediated gene silencing of V-ATPase to improve Bt cotton resistance against Pink Bollworm - Ejaz Ali; Muhammad Tariq; Idrees Ahmad Nasir; Bushra Tabassum (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Isolation, Acetylcholinesterase Inhibitory Activity, Molecular Docking, and ADME Analysis of compounds from (Afzel. ex G. Don) Benth - Samuelson Martin Luther King Boum Bindebe; Jean Noël Nyemb; Joël Abel Gbaweng Yaya; Hervé Landry Ketsemen; Syeda Abida Ejaz; Hafiz Muhammad Attaullah; Céline Henoumont; Sophie Laurent; Emmanuel Talla; Elisabeth Ngo Bum; Marcello Iriti (South African Journal of Botany, 2025)

Dynamics of urinary tract infections: a comprehensive study on antimicrobial susceptibility, virulence profiling and molecular epidemiology of uropathogenic Escherichia coli from Pakistan - Zia Ashraf; Muhammad Hidayat Rasool; Bilal Aslam; Hasan Ejaz; Fatima Mujahid; Mohsin Khurshid (Molecular Biology Reports, 2025)

Computational identification of membrane proteins for vaccine design against drug-resistant Moraxella catarrhalis - Fizza Arshad; Rania Pervaiz; Asifa Sarfraz; Hasan Ejaz; Amal Alotaibi; Riaz Ullah; Umar Nishan; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2025)

Mechanical characterization and impact resistance of concrete incorporating recycled thin-walled hollow tubular GFRP sections - Muhammad Rizwan Riaz; Muhammad Moeed Azhar; Muhammad Fahad Ejaz; Rizwan Azam; Muhammad Faraz Javaid (Innovative Infrastructure Solutions, 2025)

Genomic Insights into Poultry-Associated Staphylococcus Aureus from Haripur, Pakistan - Arif Ullah; Bushra Fatima; Mohammad Ejaz; Muhammad Ali Syed (Current Microbiology, 2025)

Turn-off Fluorimetric Detection of Fe3+ Metal Ions by a Schiff Base Probe (E)-2-(((2-hydroxy-4-sulfonaphthalen-1-yl) imino) methyl) Benzoic Acid: A Combined Experimental and Theoretical Study - Muhammad Shahbaz; Muhammad Aqib Khurshid; Muhammad Ejaz; Mazhar Amjad Gilani; Maham Saeed; Ayesha Shahzad; Sundas Shahzad; Rashid Masih; Shahzad Sharif (Journal of Fluorescence, 2025)

Synthesis, characterization, and advanced sustainable applications of copper oxide nanoparticles: a review - Muhammad Hamzah Saleem; Ujala Ejaz; Meththika Vithanage; Nanthi Bolan; Kadambot H. M. Siddique (Clean Technologies and Environmental Policy, 2025)

Plant-derived green metal nanoparticles as antibacterial, antifungal, and therapeutic agents: Advances, challenges, and perspectives - Rabia Zafar; Azeem Intisar; Muhammad Imran Din; Ahsan Sharif; Ejaz Ahmed; Adeel Afzal (Bioresource Technology Reports, 2025)

The green supply chain conundrum: exploring the interplay of practices, performance, and technology in shaping SME sustainability in developing country - Ikramuddin Junejo; Jan Muhammad Sohu; Aiza Aziz Qureshi; Saba Shaikh; Faisal Ejaz; Tahir Saeed Jagirani; Md Billal Hossain (Environment, Development and Sustainability, 2025)

Association of microplastics with lead and cadmium in soil: Land-use and temporal trends - Noreen Khalid; Muhammad Aqeel; Shiou Yih Lee; Ujala Ejaz; Ali Noman; Muhammad Faisal Maqsood; Muhammad Kashif Irshad; Mohamed A. El-Sheikh (Journal of Environmental Chemical Engineering, 2025)

Intensifying the charge transfer on N–(CxNx+1) catalysts system: A cutting–edge approach for sunlight driven hydrogen production† - Ejaz Hussain; Muhammad Jalil; Javeria Mansab; Muhammad Zeeshan Abid; Shahid Iqbal; Abeer Hashem; Amal M. Al-Mohaimeed; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Gallic acid alleviates omeprazole-induced depressive behavior and memory impairment - Noreen Samad; Natasha Manzoor; Ali Irfan; Arslan Khalid; Umer Ejaz; Bakar Bin Khatab Abbas; Syed Aun Muhammad; Gamal A. Shazly; Saima Khaliq; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Assessing Human-Wildlife Conflict in Lakki Marwat, Pakistan: Economic Impacts and People’s Perceptions - Tanveer Khan; Shakeel Ahmad; Tahir Mehmood; Sajjad Rais Khan; Daulat Ullah Khan; Salman Khan; Muhammad Ullah; Ejaz Rahim (European Journal of Wildlife Research, 2025)

Plant Growth Promoting Rhizobacteria Regulated Nutrient Uptake in Quinoa (Chenopodium Quinoa Wild) Under Nutrient-Deficient Conditions Through Solubilizing Insoluble Minerals - Ejaz Rafique; Muhammad Zahid Mumtaz; Lingling Li; Inam Ullah; Talha Ali Chohan; Muhammad Waqar Alam; Adnan Mustafa; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Integrated Application of Drought-Tolerant Phosphate Solubilizing Bacteria and Native P Source Improves P Availability with Sustainable Wheat Production - Hafiz Shahid Hussain; Saira Tabbasum; Naima Mahreen; Mahreen Yahya; Khansa Ejaz; Zoya Aslam; Muhammad Imtiaz; Ejaz ul Islam; Zahid Iqbal Sajid; Sumera Yasmin (Journal of Soil Science and Plant Nutrition, 2025)

Amendment of Tomato (Lycopersicon esculentum L.) Grown in Calcareous Soil with Spent Mushroom Substrate-derived Biochar: Improvement of Morphological, Biochemical, Qualitative Attributes, and Antioxidant Activities - Hasan Sardar; Muhammad Waqas; Aamir Nawaz; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Ayman A. Ghfar; Saikh M. Wabaidur; Sami Abou Fayssal (Journal of Soil Science and Plant Nutrition, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

KPT-330, A New Candidate Drug for Targeting NOTCH1 Overexpression in T-cell Acute Lymphoblastic Leukemia, An In Vitro and Silico Study - Fariha Naz; Saima Ejaz; Tayyaba Wali; Atiqa Nudrat; Mian Abdur Rehaman Arif; Muhammad Qandeel Waheed; Fatma Hussain; Saadiya Zia (Cell Biochemistry and Biophysics, 2025)

Organic and inorganic amendments improved the morpho-physiological and nutritional status of moringa (Moringa oleifera) genotypes - Madeeha kauser; Ejaz Ahmad Waraich; Hafeez ur Rehman; Muhammad Anwar ul Haq (Acta Physiologiae Plantarum, 2025)

Catalytic charge synergy on Ni/Sr@rTiO2 system to promote hydrogen evolution for the implementation of green energy technologies - Ejaz Hussain; Sidra Khan; Muhammad Jalil; Muhammad Zeeshan Abid; Abdul Rauf; Nagina Naveed Riaz; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Combined effect of abamectin and imidacloprid against three insects of cotton - Anam Ejaz; Ahmad Nawaz; Nazia Ehsan; Muhammad Jalal Arif (Journal of Plant Diseases and Protection, 2025)

Human Brucellosis in the Rural and Urban Population of Pakistan: Seroprevalence, Risk Factors, and Clinical Manifestations - Faisal Abbas; Shahzad Ali; Ali Muhammad; Asima Azam; Amira A. Moawad; Mohammad Ejaz; Anam Iftikhar; Maryam Dadar (Current Microbiology, 2025)

Global climate change and its impact on the distribution and efficacy of Bacillus thuringiensis as a biopesticide - Muhammad Riaz Ejaz; Samir Jaoua; Niloufar Lorestani; Farzin Shabani (Science of The Total Environment, 2025)

Unveiling the surface potential and selectivity of Ti3C2Tx/rGO adsorbents for arsenic removal from water system - Muhammad Zeeshan Abid; Khezina Rafiq; Aqsa Khan Buzdar; Muhammad Zaryab Waleed; Ejaz Hussain (Journal of Cleaner Production, 2025)

Teratological abnormalities in hard ticks (Acari: Ixodidae) from Pakistan - Ejaz Akbar; Shafi Ullah; Mashal M. Almutairi; Iram Liaqat; Muhammad Adnan; Abdulaziz Alouffi; Tetsuya Tanaka; Abid Ali (Experimental and Applied Acarology, 2025)

Assessing the Effectiveness of Audio-Visual vs. Visual Neurofeedback for Attention Enhancement: A Pilot Study with Neurological, Behavioural, and Neuropsychological Measures - Osama Ejaz; Muhammad Abul Hasan; Faryal Raees; Maham Hammad; Saad Ahmed Qazi (Brain Topography, 2025)

Environmental impacts of the billion tree Tsunami project in Khyber Pakhtunkhwa on the dynamics of Agro-Meteorological Droughts - Khalil Ur Rahman; Deqiang Mao; Nuaman Ejaz; Quoc Bao Pham; Anwar Hussain; Meriame Mohajane; Muhammad Ali; Songhao Shang (Journal of Hydrology, 2024)

The potential of local exhaust combined with mixing and displacement ventilation systems to mitigate COVID-19 transmission risks - Weixin Zhao; Muhammad Farhan Ejaz; Simo Kilpeläinen; Juha Jokisalo; Risto Kosonen (Building and Environment, 2024)

Adenosine A2AR in viral immune evasion and therapy: unveiling new avenues for treating COVID-19 and AIDS - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Sajjad Ullah; Abualgasim Elgaili Abdalla; Muhammad Ikram Ullah; Bi Bi Zainab Mazhari; Lienda Bashier Eltayeb; Ismail Hamad; Hasan Ejaz (Molecular Biology Reports, 2024)

Metagenomic approaches and opportunities in arid soil research - Muhammad Riaz Ejaz; Kareem Badr; Zahoor Ul Hassan; Roda Al-Thani; Samir Jaoua (Science of The Total Environment, 2024)

Stoichiometric and bacterial eco-physiological insights into microbial resource availability in karst regions affected by clipping-and-burning - Ansa Rebi; Guan Wang; Tao Yang; Jasper Kanomanyanga; Irsa Ejaz; Adnan Mustafa; Muhammad Rizwan; Jinxing Zhou (Journal of Environmental Management, 2024)

A cutting–edge approach to remove arsenic contents from ground water via sulfur doped copper ferrites (S–CuFe2O4) † - Ejaz Hussain; Aqsa Khan Buzdar; Muhammad Zeeshan Abid; Abdul Rauf; Khezina Rafiq (Journal of Environmental Management, 2024)

Integrated assessment of groundwater quality dynamics and Land use/land cover changes in rapidly urbanizing semi-arid region - Arif ullah; Sajjad Hussain; Yicheng Wang; Muhammad Awais; Meer Muhammad Sajjad; Nuaman Ejaz; Umar Javed; Muhammad Waqas; Xiao Zhe; Javed Iqbal (Environmental Research, 2024)

Experimental comparison of structural and active protective methods against breath- and cough-borne aerosols in a meeting room - Muhammad Farhan Ejaz; Simo Kilpeläinen; Sami Lestinen; Risto Kosonen (Building and Environment, 2024)

Xylanase from Neobacillus sedimentimangrovi UE25: Characterization, purification and applications - Rozina Rashid; Uroosa Ejaz; Syed Faraz Moin; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2024)

Multi-criteria decision-making techniques for groundwater potentiality mapping in arid regions: A case study of Wadi Yiba, Kingdom of Saudi Arabia - Nuaman Ejaz; Aftab Haider Khan; Muhammad Waqar Saleem; Amro Mohamed Elfeki; Khalil Ur Rahman; Sajjad Hussain; Safi Ullah; Songhao Shang (Groundwater for Sustainable Development, 2024)

Enhancing drought tolerance in broccoli (Brassica oleracea L.) through melatonin application: Physiological and biochemical insights into growth, photosynthesis, and antioxidant defense mechanisms - Hasan Sardar; Muhammad Shafiq; Safina Naz; Sajid Ali; Riaz Ahmad; Shaghef Ejaz (Biocatalysis and Agricultural Biotechnology, 2024)

Analyzing the Role of Changing Climate on the Variability of Intensity-Duration-Frequency Curve Using Wavelet Analysis - Syed Adnan Shah; Hamza Farooq Gabriel; Muhammad Waqar Saleem; Nuaman Ejaz; Songhao Shang; Deqiang Mao; Khalil Ur Rahman (Water Resources Management, 2024)

Unveiling the impact of textile materials to prevent viral infections: Urgency for awareness and public safety† - Muhammad Zaryab Waleed; Khezina Rafiq; Muhammad Zeeshan Abid; Muhammad Burhan; Raed H. Althomali; Shahid Iqbal; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2024)

Assessment of textile effluent treatment by immobilized Trametes pubescens MB 89 for plant growth promotion - Uroosa Ejaz; Saima Zakir; Zainul Abideen; Bushra Fahim; Waniya Shaikh; Faryal Shakil; Fizza Haroon Mirza; Syed Wasi Haider; Adnan Khan; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

Unraveling the impact of wildfires on permafrost ecosystems: Vulnerability, implications, and management strategies - Ansa Rebi; Guan Wang; Muhammad Irfan; Azfar Hussain; Adnan Mustafa; Trevan Flynn; Irsa Ejaz; Taqi Raza; Parsa Mushtaq; Muhammad Rizwan; Jinxing Zhou (Journal of Environmental Management, 2024)

Temperature, topography, woody vegetation cover and anthropogenic disturbance shape the orchids distribution in the western Himalaya - Karamit Hussain; Muhammad Ejaz-Ul-Islam Dar; Arshad Mahmood Khan; Taskeen Iqbal; Ansar Mehmood; Tariq Habib; Ihab Mohamed Moussa; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2024)

Zinc sulfate as a draw solute in forward osmosis and its regeneration by reagent precipitation - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Kew-Ho Lee (Desalination, 2024)

Investigation of novel bacteriocin producers of Bacillus thuringiensis and partial characterization of two new bacteriocins: Thuricin 466 and thuricin 4Q7 - Minoli Nitin Doshi; Kareem Badr; Muhammad Ejaz; Zahoor Ul Hassan; Samir Jaoua (Bioresource Technology Reports, 2024)

Soil Application of Potassium Maintains Growth, Water Relations, Yield and Seed Quality of Quinoa in Salt Affected Soils - Mehmood Ejaz; Muhammad Amir Bakhtavar; Shahid Iqbal; Mahmood Alam Khan; Raheela Jabeen; Nazish Jabeen; Ali Raza (Journal of Crop Health, 2024)

Surface sensitization of TiO2 via Pd/Rb2O cocatalysts: Mechanistic insights to the arsenic elimination from ground drinking water† - Kashaf Ul Sahar; Khezina Rafiq; Muhammad Zeeshan Abid; Ubaid ur Rehman; Ujala Quyyum; Abdul Rauf; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2023)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

Synergistic effect of extracellular adenosine triphosphate and quercetin on post-thaw quality and fertilization potential of Lohi ram sperm - Muhammad Tayyab Khan; Muhammad Irfan-ur-Rehman Khan; Ejaz Ahmad; Muhammad Rizwan Yousaf; Muhammad Oneeb (Cryobiology, 2023)

A comprehensive study of the sources, extraction methods and structures of the Saponin compounds for its antidiabetic activity - Muhammad Umair Afzal; Muhammad Pervaiz; Anam Ejaz; Eisha Bajwa; Sadaf Naz; Zohaib Saeed; Sami Ullah; Syeda Shaista Gillani; Rana Rashad Mehmood Kan; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Nanotechnologies for environmental remediation and their ecotoxicological impacts - Mahnoor Ejaz; Alvina Gul; Munir Ozturk; Ahmed Hafeez; Bengu Turkyilmaz Unal; Sami Ullah Jan; Muhammad Taimur Siddique (Environmental Monitoring and Assessment, 2023)

Corrigendum to cerium oxide nanoparticles alleviates stress in wheat grown on Cd contaminated alkaline soil [Chemosphere 338 (2023) 139561] - Muhammad Ashar Ayub; Hamaad Raza Ahmad; Muhammad Zia ur Rehman; Ejaz Ahmad Waraich (Chemosphere, 2023)

Cerium oxide nanoparticles alleviates stress in wheat grown on Cd contaminated alkaline soil - Muhammad Ashar Ayub; Hamaad Raza Ahmad; Muhammad Zia ur Rehman; Ejaz Ahmad Waraich (Chemosphere, 2023)

Exogenous melatonin mitigates chilling injury in zucchini fruit by enhancing antioxidant system activity, promoting endogenous proline and GABA accumulation, and preserving cell wall stability - Sajid Ali; Aamir Nawaz; Safina Naz; Maratab Ali; Shaghef Ejaz; Muhammad Azam; Kashif Razzaq (Postharvest Biology and Technology, 2023)

“Garlic and ginger extracts mediated green synthesis of silver and gold nanoparticles: A review on recent advancements and prospective applications’’ - Zohaib Saeed; Muhammad Pervaiz; Anam Ejaz; Shah Hussain; Shumila Shaheen; Behram Shehzad; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Cold and Drought Stresses in Wheat: A Global Meta-analysis of 21st Century - Irsa Ejaz; Xiaoyu Pu; Muhammad Asad Naseer; Yves N.’Dri Bohoussou; Ying Liu; Muhammad Farooq; Jingting Zhang; Yinghua Zhang; Zhimin Wang; Zhencai Sun (Journal of Plant Growth Regulation, 2023)

Colloidal gold based immunochromatographic detection of Mycoplasmopsis synoviae infection and its prevalence in avian species of Karachi, Pakistan - Nida Rehman; Uroosa Ejaz; Amal Siraj; Shazma Liaquat; Muhammad Sohail; Taseer Ahmed Khan; Syed Faraz Moin; Aqeel Ahmad (Research in Veterinary Science, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Holistic expression of miR-17-92 cluster in obesity, kidney diseases, cardiovascular diseases, and diabetes - Maheen Ejaz; Syed Mohammad Usman; Saira Amir; Muhammad Jawad Khan (Molecular Biology Reports, 2023)

Exogenous Application of Melatonin Improves the Growth and Productivity of Two Broccoli (Brassica oleracea L.) Cultivars Under Salt Stress - Hasan Sardar; Muhammad Arif Ramzan; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Muhammad Ahsan Altaf (Journal of Plant Growth Regulation, 2023)

Unveiling the genomic potential of a novel thermostable glycoside hydrolases producing Neobacillus sedimentimangrovi UE25 - Uroosa Ejaz; Faizan Saleem; Rozina Rashid; Khwaja Ali Hasan; Muhammad Noman Syed; Muhammad Sohail (Antonie van Leeuwenhoek, 2023)

Transgenic maize inbred lines expressing high levels of Bacillus thuringiensis vegetative insecticidal protein (Vip3Aa86) offer effective control of maize stem borer (Chilo partellus) - Muhammad Umar Bhatti; Bushra Tabassum; Colin Berry; Anwar Khan; Uzma Qaisar; Ejaz Ali; Rida Khalid; Abdul Munim Farooq; Muhammad Tariq; Hasan Ayaz (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Dose optimization of silicon for boosting arbuscular mycorrhizal fungi colonization and cadmium stress mitigation in maize (Zea mays L.) - Ubaid Ullah Zia; Abdul Rehman Niazi; Zahoor Ahmad; Hesham F. Alharby; Ejaz Ahmad Waraich; Asim Abbasi; Muhammad Aamir Iqbal; Sarfraz Ahmed; Shozab Hina (Environmental Science and Pollution Research, 2023)

Efficacious use of potential biosurfactant producing plant growth promoting rhizobacteria to combat petrol toxicity in Zea mays L. plants - Sabiha Habib; Ambreen Ahmed; Muhammad Farhan Ul Haque; Rabia Ejaz (Environmental Science and Pollution Research, 2023)

Exogenous Application of Thiourea Improves the Growth, Seed Yield, and Seed Fatty Acid Profile in Late Sown Camelina - Muhammad Ahmad; Ejaz Ahmad Waraich; Saddam Hussain; Usman Zulfiqar; Fitsum Tilahun Teshome; Manuel Gastelbondo; Muhammad Imran; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Physiological Mechanisms of Grain Yield Loss Under Combined Drought and Shading Stress at the Post-silking Stage in Maize - Muhammad Asad Naseer; Zhang Nengyan; Irsa Ejaz; Sadam Hussain; Muhammad Ahsan Asghar; Muhammad Farooq; Qian Rui; Abd Ullah; Chen Xiaoli; Ren Xiaolong (Journal of Soil Science and Plant Nutrition, 2023)

Thiourea Application Increases Seed and Oil Yields in Camelina Under Heat Stress by Modulating the Plant Water Relations and Antioxidant Defense System - Muhammad Ahmad; Ejaz Ahmad Waraich; Usman Zulfiqar; Aman Ullah; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Multipurpose plants utilization and resource management in Musk Deer National Park, Western Himalayas of Kashmir - Farooq Ahmed; Muhammad Ejaz Ul Islam Dar; Muhammad Jamil Ahmed; Tariq Habib; Liaquat Ali Khan (Environment, Development and Sustainability, 2023)

Zeolite amendment reduces lead accumulation and improves growth and yield in tomato plants irrigated with sewage water - Rashid Jawad; Aamir Nawaz; Shaghef Ejaz; Sajid Ali; Muhammad Shahzad Saleem; Hafiz Mohkum Hammad (Environmental Science and Pollution Research, 2023)

Two-way strategy for enhanced pectinase production: Random mutagenesis and utilization of a halophytic biomass - Asma Hanif; Uroosa Ejaz; Khwaja Ali Hasan; Malaika Karim; Fehmida Suleman; Muskan Siddiq; Syed Faraz Moin; Zainul Abideen; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2023)

Analyzing the impact of drought on agriculture: evidence from Pakistan using standardized precipitation evapotranspiration index - Anwar Hussain; Khan Zaib Jadoon; Khalil Ur Rahman; Songhao Shang; Muhammad Shahid; Nuaman Ejaz; Himayatullah Khan (Natural Hazards, 2023)

Adenosine A2A receptor as a potential target for improving cancer immunotherapy - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Muhammad Ikram Ullah; Ayman Ali Mohammed Alameen; Muhammad Imran; Hasan Ejaz (Molecular Biology Reports, 2022)

Exploring thiazole-linked thioureas using alkaline phosphatase assay, biochemical evaluation, computational analysis and structure–activity relationship (SAR) studies - Sajid Ali Channar; Pervaiz Ali Channar; Aamer Saeed; Aisha A. Alsfouk; Syeda Abida Ejaz; Rabail Ujan; Razia Noor; Muhammad Sajjad Bilal; Qamar Abbas; Zahid Hussain; Bilal Ahmad Khan; Hussain Raza; et al. (Medicinal Chemistry Research, 2022)

Improving Heat Stress Tolerance in Camelina sativa and Brassica napus Through Thiourea Seed Priming - Muhammad Ahmad; Ejaz Ahmad Waraich; Saddam Hussain; Choudhary Muhammad Ayyub; Zahoor Ahmad; Usman Zulfiqar (Journal of Plant Growth Regulation, 2022)

Thiourea Application Improves the Growth and Seed and Oil Yields in Canola by Modulating Gas Exchange, Antioxidant Defense, and Osmoprotection Under Heat Stress - Muhammad Ahmad; Ejaz Ahmad Waraich; Usman Zulfiqar; Saddam Hussain; Muhammad Umair Yasin; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2022)

Contribution of structural and functional adaptations of hyper-accumulator Suaeda vera Forssk. ex J.F. Gmel. for adaptability across salinity gradients in hot desert - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Syed Mohsan Raza Shah; Faakeha Islam; Iftikhar Ahmad; Farial Ejaz; Mehwish Naseer (Environmental Science and Pollution Research, 2022)

Effect of soil amendments and varied soil texture on wheat growth, physiology, and nutrient accumulation at different salinity: sodicity levels - Ayesha Abdul Qadir; Ghulam Murtaza; Muhammad Zia-ur-Rehman; Ejaz Ahmad Waraich (Arabian Journal of Geosciences, 2022)

Application of Gypsum or Sulfuric Acid Improves Physiological Traits and Nutritional Status of Rice in Calcareous Saline-Sodic Soils - Ayesha Abdul Qadir; Ghulam Murtaza; Muhammad Zia-ur-Rehman; Ejaz Ahmad Waraich (Journal of Soil Science and Plant Nutrition, 2022)

Modelling Climate Uncertainty and Adaptations for Soybean-Based Cropping System - Maryam Ejaz; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Muhammad Ali Raza; Ahmed M. S. Kheir; Mukhtar Ahmed; Khair Muhammad Kakar; Shakeel Ahmad (International Journal of Plant Production, 2022)

Volkamer Lemon Tetraploid Rootstock Transmits the Salt Tolerance When Grafted with Diploid Kinnow Mandarin by Strong Antioxidant Defense Mechanism and Efficient Osmotic Adjustment - Muhammad Fasih Khalid; Raphael Morillon; Muhammad Akbar Anjum; Shaghef Ejaz; Muhammad Junaid Rao; Shakeel Ahmad; Sajjad Hussain (Journal of Plant Growth Regulation, 2022)

Assessment of cobalt in wheat grains as affected by diverse fertilizers: implications for public health - Abid Ejaz; Kafeel Ahmad; Zafar Iqbal Khan; Shahzad Akhtar; Razia Sultana; Muhammad Nadeem; Muhammad Iftikhar Hussain; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Appraising growth, daily intake, health risk index, and pollution load of Zn in wheat (Triticum aestivum L.) grown in soil differentially spiked with zinc - Abid Ejaz; Zafar Iqbal Khan; Kafeel Ahmad; Fatima Ghulam Muhammad; Shahzad Akhtar; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Evaluating the impact of the environment on depleting groundwater resources: a case study from a semi-arid and arid climatic region - Khalil Ur Rahman; Anwar Hussain; Nuaman Ejaz; Muhammad Shahid; Zheng Duan; Babak Mohammadi; Pham Ngoc Hoai; Quoc Bao Pham; Khaled Mohamed Khedher; Duong Tran Anh (Hydrological Sciences Journal, 2022)

Evaluation of nickel toxicity in wheat as function of diverse type of fertilizers: implications for public health - Abid Ejaz; Kafeel Ahmad; Zafar Iqbal Khan; Razia Sultana; Shahzad Akhtar; Muhammad Nadeem (Environmental Science and Pollution Research, 2022)

Cadmium Toxicity in Plants: Recent Progress on Morpho-physiological Effects and Remediation Strategies - Usman Zulfiqar; Aqsa Ayub; Saddam Hussain; Ejaz Ahmad Waraich; Mohamed A. El-Esawi; Muhammad Ishfaq; Muhammad Ahmad; Nauman Ali; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2022)

A study on the contamination assessment, health risk and mobility of two heavy metals in the soil-plants-ruminants system of a typical agricultural region in the semi arid environment - Xiaoping Ge; Zafar Iqbal Khan; Fu Chen; Mubeen Akhtar; Kafeel Ahmad; Abid Ejaz; Muhammad Arslan Ashraf; Muhammad Nadeem; Shahzad Akhtar; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Constituents and antibacterial activity of leaf essential oil of Plectranthus scutellarioides - Pakeeza Aziz; Nadeem Muhammad; Azeem Intisar; Muhammad Amin Abid; Muhammad Imran Din; Muhammad Yaseen; Rehana Kousar; Aqsa Aamir; Quratulain; Rabia Ejaz (Plant Biosystems, 2021)

Biochemical investigation of human exposure to aflatoxin M1 and its association with risk factors of diabetes mellitus - Muhammad Sajid Hamid Akash; Muhammad Ejaz ul Haq; Abdul Qader; Kanwal Rehman (Environmental Science and Pollution Research, 2021)

Sources, chemistry, bioremediation and social aspects of arsenic-contaminated waters: a review - Syed Ejaz Hussain Mehdi; Rabia Amen; Awais Ali; Hirra Anjum; Abid Mahmood; Muhammad Mubashir; Ahmad Mukhtar; Sami Ullah; Abdullah G. Al-Sehemi; Muhammad Ibrahim; Mohd Shariq Khan; Muhammad Abdul Qyyum; et al. (Environmental Chemistry Letters, 2021)

Sewage wastewater reclamation with sand column filter and reduction of heavy metal accumulation in tomato and okra - Safina Naz; Muhammad Akbar Anjum; Shaghef Ejaz; Sajid Ali; Bushra Saddiq; Hasan Sardar; Sakeena Tul-Ain Haider (Environmental Science and Pollution Research, 2021)

Evaluation of transfer of lead in soil plant animal system: assessment of consequences of its toxicity - Fu Chen; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Tasneem Ahmad; Ifra Saleem Malik; Asma Ashfaq; Mudasra Munir; Sonaina Nazar; Zunaira Munir; Abid Ejaz; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Foliar Applied Thiourea Improved Physiological Traits and Yield of Camelina and Canola Under Normal and Heat Stress Conditions - Muhammad Ahmad; Ejaz Ahmad Waraich; Asif Tanveer; Muhammad Anwar-ul-Haq (Journal of Soil Science and Plant Nutrition, 2021)

Relative Effectiveness of Phosphorus and Potassium Along with Compost and Organic Acids on Maize Crop Grown in Calcareous Soil: a Multivariate Analysis - Saira Tabbasum; Muhammad Akhtar; Nadeem Sarwar; Muhammad Imran Tipu; Wasiq Ikram; Arooba Ashraf; Amjad Ejaz; Behzad Murtaza; Muhammad Rizwan Khan (Journal of Soil Science and Plant Nutrition, 2021)

Spatiotemporal analysis of crop water requirements in Lower Chenab Canal (LCC) Irrigation System for the better management of water resources - Muhammad Usman; Ejaz Hussain; Umair Rabbani; Shahid Ghazi; Syed M. Irteza; Shamaila Gull (Arabian Journal of Geosciences, 2021)

Evaluation of Factors Affecting Saccharification of Sugarcane Bagasse Using Cellulase Preparation from a Thermophilic Strain of Brevibacillus sp. - Maria Tariq Khan; Uroosa Ejaz; Muhammad Sohail (Current Microbiology, 2020)

Co-culturing corncob-immobilized yeasts on orange peels for the production of pectinase - Faizan Qadir; Uroosa Ejaz; Muhammad Sohail (Biotechnology Letters, 2020)

Human exposure to bisphenol A through dietary sources and development of diabetes mellitus: a cross-sectional study in Pakistani population - Muhammad Ejaz Ul Haq; Muhammad Sajid Hamid Akash; Shakila Sabir; Malik Hassan Mahmood; Kanwal Rehman (Environmental Science and Pollution Research, 2020)

Linking traditional anti-ulcer use of rhizomes of Bergenia ciliata (Haw.) to its anti-Helicobacter pylori constituents - Ejaz Ali; Najma Arshad; Nadeem Irfan Bukhari; Muhammad Nawaz Tahir; Shamail Zafar; Amjad Hussain; Sajida Parveen; Shaista Qamar; Naureen Shehzadi; Khalid Hussain (Natural Product Research, 2020)

Revealing heterogeneous causal links among financial development, construction industry, energy use, and environmental quality across development levels - Munir Ahmad; Gul Jabeen; Muhammad Khizar Hayat; Rana Ejaz Ali Khan; Shoaib Qamar (Environmental Science and Pollution Research, 2020)

Role of phosphorous mining in mobilization and bioaccessibility of heavy metals in soil-plant system: Abbottabad, Pakistan - Afshan; Sajjad Ahmad; Muhammad Imran; Rab Nawaz; Muhammad Arshad; Muhammad Ejaz Ul Islam Dar; Muhammad Hussnain Siddque; Muhammad Nadeem; Liaqat Ali (Arabian Journal of Geosciences, 2019)

Quantifying climate internal variability using an hourly ensemble generator over South Korea - Jongho Kim; Muhammad Ejaz Tanveer; Deg-Hyo Bae (Stochastic Environmental Research and Risk Assessment, 2018)

Resistance in field populations of Amrasca devastans (Hemiptera: Cicadellidae) to new insecticides in Southern Punjab, Pakistan - Nasir Abbas; Naeem Abbas; Masood Ejaz; Sarfraz Ali Shad; Iqra Asghar; Aima Irum; Muhammad Binyameen (Phytoparasitica, 2018)

Pluronic-Based Mixed Polymeric Micelles Enhance the Therapeutic Potential of Curcumin - Muhammad Usman Akbar; Khalid Mahmood Zia; Ahsan Nazir; Jamshed Iqbal; Syeda Abida Ejaz; Muhammad Sajid Hamid Akash (AAPS PharmSciTech, 2018)

Ensembling Downscaling Techniques and Multiple GCMs to Improve Climate Change Predictions in Cryosphere Scarcely-Gauged Catchment - Muhammad Azmat; Muhammad Uzair Qamar; Shakil Ahmed; Muhammad Adnan Shahid; Ejaz Hussain; Sajjad Ahmad; Rao Arsalan Khushnood (Water Resources Management, 2018)

Assessment of field evolved resistance to some broad-spectrum insecticides in cotton jassid, Amrasca devastans from southern Punjab, Pakistan - Nasir Abbas; Muhammad Ismail; Masood Ejaz; Iqra Asghar; Aima Irum; Sarfraz Ali Shad; Muhammad Binyameen (Phytoparasitica, 2018)

Physiological responses of wheat to drought stress and its mitigation approaches - Zahoor Ahmad; Ejaz Ahmad Waraich; Sajjad Akhtar; Shazia Anjum; Tanveer Ahmad; Wajid Mahboob; Osama Bin Abdul Hafeez; Terence Tapera; Maryke Labuschagne; Muhammad Rizwan (Acta Physiologiae Plantarum, 2018)

Assessing the combined toxicity of conventional and newer insecticides on the cotton mealybug Phenacoccus solenopsis - Bushra Saddiq; Masood Ejaz; Sarfraz Ali Shad; Muhammad Aslam (Ecotoxicology, 2017)

Structural and functional characteristics of plant proteinase inhibitor-II (PI-II) family - Shazia Rehman; Ejaz Aziz; Wasim Akhtar; Muhammad Ilyas; Tariq Mahmood (Biotechnology Letters, 2017)

Trypsinized Cry1Fa and Vip3Aa have no detrimental effects on the adult green lacewing Chrysopa pallens (Neuroptera: Chrysopidae) - Intazar Ali; Shuai Zhang; Muhammad Iqbal; Samina Ejaz; Jin-jie Cui (Applied Entomology and Zoology, 2017)

The impact of CO2 emissions on economic growth: evidence from selected higher CO2 emissions economies - Muhammad Azam; Abdul Qayyum Khan; Hussin Bin Abdullah; Muhammad Ejaz Qureshi (Environmental Science and Pollution Research, 2016)

Foliar NK application mitigates drought effects in sunflower (Helianthus annuus L.) - Rai Altaf Hussain; Rashid Ahmad; Fahim Nawaz; Muhammad Yasin Ashraf; Ejaz Ahmad Waraich (Acta Physiologiae Plantarum, 2016)

Investigation of temporal change in glacial extent of Chitral watershed using Landsat data - Usman Ali Naeem; Muhammad Ali Shamim; Naeem Ejaz; Habib ur Rehman; Umer Mustafa; Hashim Nisar Hashmi; Abdul Razzaq Ghumman (Environmental Monitoring and Assessment, 2016)

Removal of Cd, Cr, and Pb from aqueous solution by unmodified and modified agricultural wastes - Muhammad Mahmood-ul-Hassan; Vishandas Suthor; Ejaz Rafique; Muhammad Yasin (Environmental Monitoring and Assessment, 2015)

Monitoring impacts of air pollution: PIXE analysis and histopathological modalities in evaluating relative risks of elemental contamination - Sohail Ejaz; Gerry Amor Camer; Khaleeq Anwar; Muhammad Ashraf (Ecotoxicology, 2014)

MRI and neuropathological validations of the involvement of air pollutants in cortical selective neuronal loss - Sohail Ejaz; Khaleeq Anwar; Muhammad Ashraf (Environmental Science and Pollution Research, 2014)

Cytotoxic, phytotoxic, and mutagenic appraisal to ascertain toxicological potential of particulate matter emitted from automobiles - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Imran Altaf; Aftab Ahmad Anjum (Environmental Science and Pollution Research, 2013)

Monitoring trace elements generated by automobiles: air pollutants with possible health impacts - Khaleeq Anwar; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2013)

Characterization of tannery effluent wastewater by proton-induced X-ray emission (PIXE) analysis to investigate their role in water pollution - Lubna Shakir; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2012)

Relationship of age to body weight, scrotal circumference, testicular ultrasonograms, and semen quality in Sahiwal bulls - Ejaz Ahmad; Nasim Ahmad; Zahid Naseer; Muhammad Aleem; Muhammad Sarwar Khan; Muhammad Ashiq; Muhammad Younis (Tropical Animal Health and Production, 2011)

Elaeagnoside, chymotrypsin inhibiting steroidal glucoside from Elaeagnus orientalis - Muhammad Ayaz; Muhammad Riaz; Abdul Malik; Ejaz Ahmad; Itrat Fatima; Muhammad Arif Lodhi; Muhammad Iqbal Chaudhary (Natural Product Research, 2009)

A pharmacological and toxicological evaluation of Haloxylon recurvum - Abdul Wahab; Ejaz Ahmed; Sarfraz Ahmad Nawaz; Ahsan Sharif; Rizwan Ul Haq; Abdul Malik; Muhammad Iqbal Choudhary; Mohsin Raza (Natural Product Research, 2008)

Chymotrypsin inhibitory constituents from Haloxylon recurvum - Ejaz Ahmed; Abdul Malik; Nighat Afza; Naheed Riaz; Itrat Anis; Ahsan Sharif; Sadia Farheen; Muhammad Arif Lodhi; Muhammad Iqbal Choudhary (Natural Product Research, 2007)

Bread wheat varieties as influenced by different nitrogen levels - Iqtidar Hussain; Muhammad Ayyaz Khan; Ejaz Ahmad Khan (Journal of Zhejiang University-SCIENCE B, 2006)

Response of three wheat genotypes grown under saline medium to low/high potassium levels - M. U. Shirazi; B. Khanzada; Muhammad Ali; Ejaz ul Islam; S. M. Mujtaba; R Ansari; S. M. Alam; M. A. Khan; Mukhtiar Ali (Acta Physiologiae Plantarum, 2002)